Does MtDNA Nucleoid Organization Impact Aging? - Bogenhagen, Daniel F. (2009)
Somatic cells in tissue culture package several copies of mitochondrial DNA (mtDNA) in aggregates known as nucleoids that appear to be remarkably stable. The clustering of multiple mtDNA genomes in a single nucleoid complex may promote the progressive age-related accumulation of deletion and point mutations in mtDNA in many somatic tissues, particularly in post-mitotic cells. In contrast, oocytes appear to have the ability to select against deleterious mutations in mtDNA, at least in mice. This fundamental difference suggests that oocytes may be better able to detect and remove defective mtDNA genomes than somatic cells, possibly due in part to the simpler organization of the mtDNA in smaller nucleoids. These observations suggest the hypothesis that a complex nucleoid structure containing several mtDNA molecules may impair the ability of the cell to select against deleterious mtDNA mutations, thereby contributing to age-related mitochondrial dysfunction.